The co-existence of membranoproliferatA +/- ve glomerulonephritis type 1 and coeliac disease: a case report - ALPAY, HARİKA; GÖKCE, İBRAHİM (SPRINGER, 2009)
Coeliac disease is an autoimmune enteropathy characterised by chronic inflammation of the small intestinal mucosa and the presence of typical autoantibodies. Coeliac disease may be a risk factor for renal disease. Immunoglobulin A (IgA) nephropathy is reported in the majority of these cases. Only one adult patient had been reported with membranoproliferative glomerulonephritis (MPGN) and coeliac disease. Here, we report a case in a 12-year-old girl with coeliac disease who presented with severe anaemia and later developed nephrotic syndrome. Renal biopsy of the patient was consistent with MPGN type 1, which has not been previously reported in children with coeliac disease. A gluten-free diet was started. After 6 months of this diet, her nephrotic syndrome resolved completely. This case is presented to draw attention to the rare association of coeliac disease and MPGN type 1.
Keywords: Membranoproliferative glomerulonephritis; Coeliac disease; Child; Nephrotic syndrome; NEPHROPATHY; DISORDERS